POAC-based Principal Management Model in Planning the PAUD Unit Annual Program - Indrawati Indrawati; Wahira Wahira (Asha Publishing, 2025)
This study presents a systematic literature review of the POAC (Planning, Organizing, Actuating, and Controlling) management model as a strategic approach to planning the annual programs of PAUD (Pendidikan Anak Usia Dini) units. The review examines how each component of the POAC model contributes to enhancing leadership, improving the quality of planning, and facilitating program implementation in early childhood education settings. Through an extensive thematic analysis of peer-reviewed literature published between 2018 and 2024, the study identifies patterns, strengths, and practical challenges associated with the application of the model in PAUD institutions. Findings indicate that POAC-based management enhances administrative coordination, fosters participative leadership, and supports effective monitoring mechanisms. However, gaps persist in empirical evidence linking POAC to measurable child developmental outcomes, particularly in low-resource educational environments. The study recommends future research that integrates POAC with local context-specific strategies and calls for more evidence on its pedagogical impacts. Overall, this review affirms POAC's potential as a valuable framework for improving the governance and quality of early childhood education in Indonesia.